Sleep Quality in the Admitted Elderly: A Prospective Observational Study in Eastern India - Shatavisa Mukherjee; Nikhil Era; Ritika Singh; Pankaj Hans; Uttam Paul; Susanta Bordoloi (Bengal Physician Journal)
Background: With declining age, elderly admissions are encountered with sleep disturbances during the hospital stay. Poor sleep health can adversely affect many organ functions causing a weakened immune system, increased adverse cardiovascular events, impaired cognitive function, and increased fall risk and frailty in the elderly. The present study tried to address the issue of sleep quality in admitted elderly patients in a hospital setup. Materials and methods: A prospective observational study was conducted among the elderly inpatients of a few tertiary care setups in Eastern India. Patients were personally interviewed to evaluate the history of sleep quality at home, sleep quality after the first and the third days of admission, and potential associated factors. The Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep quality in the subjects. Patient-reported factors contributing to poor sleep health were noted. Data were statistically analyzed. Results: Sleep efficiency is significantly affected by hospital stay. The global PSQI score conferred poor sleep quality in 51.05% elderly in baseline, 58.64% after the first night of hospitalization, and 62.86% after the third night of hospitalization. Sleep quality was assessed using PSQI questionnaire. Prolonged sleep latency and decreased total sleep duration were noted among study participants at the third time point in comparison with the first. Factors like doctor–nurse interruption, pain, light, and noise as some of the most frequently reported factors contributed to poorer sleep. Higher age, infrequent physical activity, previous history of hospitalization, anxiety, and depressive state were significantly associated with higher odds of poor sleep quality. Conclusion: The study demonstrated that overall sleep quality was significantly affected during hospital stay in older adults. Patient-reported factors contributing toward poorer sleep health must be intervened in order to achieve better treatment outcomes in the elderly.